Analisis Strategi Penyelesaian Pembiayaan Bermasalah Terhadap Produk Murabahan dalam Persfektif Ekonomi Islam: Studi Kasus Pada BSI KCP Cemara Asri - Pohan, Hasmidar; Nasution, Muhammad Lathief Ilhamy (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2023)
This study aims to analyze problem solving strategies in financing murabaha products from an Islamic economic perspective at BSI KCP Cemara Asri. The method used in this research is a qualitative approach with data collection techniques through interviews, observation, and document studies. The results of the study indicate that there are problems in financing murabaha transactions at Bank BSI KCP Cemara Asri, where internal and external factors are the main causes of problems in these murabahah transactions. However, through the implementation of appropriate financing handling strategies, these problems can be resolved effectively. In a review of the sharia economic perspective, the implementation of murabahah financing at the BSI Cemara Asri branch complies with the regulations set by the National Sharia Council (DSN) and the Indonesian Ulema Council (MUI). As a recommendation, the researchers suggest that the BSI Cemara Asri branch develop murabahah financing products more broadly, not just limited to land and building financing.